The Effect of Pempek Culture-Based Learning Approach on Children's Ability to Recognise Numbers Aged 5-6 Years - Maida; Ilhami, Akmilah (Yayasan Corolla Education Centre, 2025)
The goal of this study is to find out how the Culturally Responsive Teaching (CRT) method based on pempek affects the number symbol recognition skills of children at PAUD Permata Kasih who are between the ages of five and six. To administer therapy without a control group, a pre-experiment with a one group pretest-posttest design. This was followed by a post-test. The 16 students in class B—eight males and eight girls—were the research subjects. The data obtained were analyzed using a one-sample t-test. The results of the t-test calculation show that the calculated t-value (3.28) is greater than the t-table value (1.75), thus Ha is accepted and Ho is rejected. It can be concluded that there is an effect of the Culturally Responsive Teaching (CRT) activities themed pempek at PAUD Permata Kasih. Additionally, this activity also develops other aspects such as social-emotional aspects by training children's patience in waiting in line and fine motor skills by involving the coordination of small muscle movements of the eyes and hands.